Genomics-assisted breeding for drought tolerance in cowpea - Chamarthi, S.K.; Belko, N.; Togola, A.; Fatokun, C.A.; Boukar, O. (Springer, 2019)
The importance of cowpea, Vigna unguiculata, in human and animal nutrition and sustainability of soil fertility are recognized globally especially in sub-Saharan Africa (SSA) where the crop is mainly produced in the Savanna and the Sahelian agro ecologies. However, cowpea productivity is adversely affected by both biotic (insect pests, diseases, parasitic weeds, nematodes) and abiotic (drought, heat, low soil fertility) constraints. Appreciable progress has been made in the improvement of cowpea for resistance to some biotic stresses particularly diseases such as bacterial blight, ashy stem blight, marcophomina, parasitic weeds like Striga and Alectra and some insects like aphid, leaf and flower thrips among others. There is need for intensifying research activities with focus on improving cowpea resistance to abiotic stresses. As a crop grown commonly in arid regions, cowpea is subjected to seedling stage, midseason and terminal droughts. In the recent past, the amount of rainfall, during the cropping season in the dry savannah regions of SSA, is getting less. Consequently the cropping season is getting shorter occasioned by late commencement or early cessation of the rain. Farmers in the cowpea producing areas of SSA generally have no access to irrigation hence their crops are grown under rain-fed conditions. With the impending higher frequency of drought in the dry savannah region due to climate change, efforts should be made in developing climate resilient cowpea varieties that farmers will grow. Efforts have been made in enhancing tolerance to drought in some improved cowpea varieties using conventional breeding but progress has been slow in this regard. Drought tolerance is a complex trait and many genes are involved in its inheritance. Pyramiding of these genes in improved varieties would therefore, be desirable. Such varieties with pyramided genes are likely to be stable in performance over the years and across several locations in the savannahs. Recent developments in molecular biology could play significant role in the development of such resilient varieties. In a number of crops, molecular markers associated with resistance loci have been identified and are being used in marker assisted breeding. Marker assisted backcrossing (MABC) is the choice when single traits that are simply inherited are to be moved to varieties with superior performance but lacking in the trait being transferred. Also, marker assisted recurrent selection (MARS) has shown promise in accumulating multiple genes in improved varieties of some crops. Some work has been initiated in cowpea on the use of MARS to pyramid resistance to Striga, yield and drought. Results obtained so far show the potential of this method in pyramiding desirable genes in cowpea. As more resources get committed to cowpea research a solid foundation would be established for the generation of molecular tools that should facilitate their routine application to the improvement of the crop.